Penerapan LKPD Berbasis Android Untuk Meningkatkan Pernerapan Metode Klasisfikasi ABC pada Sistem Informasi Persediaan Berbasis Website (Studi Kasus : Usaha Dagang Bangun Tani) - Hotma Taruli Silaen; Mardhiah Fadhli (Politeknik Caltex Riau, 2021)
Bangun Tani Trading Business is an individual-owned business thatsells various types of fertilizers, pesticides, and herbicides. The BangunTani Trade Business is located on Jl. Lintas Pujud, Kecamatan Siarang-arang, Kabupaten Rokan Hilir , Provinsi Riau. The Bangun Tanibusiness has not yet implemented an information system for managinginventory. A warehouse is a place used to store and put items owned bythe store. There are so many activities carried out in the warehousesuch as data collection of items to the preparation of items. The problemfaced in implementing this program is that data management is stillused manually, such as calculating the items in the warehouse directlyand the inefficient layout of the items in the warehouse. From theseproblems, a website-based inventory information system will be builtusing the ABC Classification method. This information system willproduce recommendations for items that are often sold so that they canbe arranged efficiently in the warehouse. With this information system,it is hoped that it can help shop owners in managing their warehouses.